DAYA MEMBUNUH CACING EKSTRAK BIJI PEPAYA (CARICA PAPAYA) PADA AYAM BURAS - Marlin R. K. Yowi; Devi Y. J. A. Moenek; Tri A. Y. Foenay (Politeknik Pertanian Negeri Kupang, 2009)
Power Kills Papaya Seed Extract Worm (Carica Papaya) In Chicken Buras. A research as a mean to proves and determines effective concentration (Efective Concentration/EC50) from papaw seed extract (Carica papaya) to kill Ascaridia galli has been executed in Oeba Market of Kupang and Animal Healthy Laboratory of Politeknik Pertanian Negeri Kupang. In this research applied papaw seed extract coming from local papaw tree and worm Ascaridia galli is coming from chicken intestine buras from place of cutting of chicken Pasar Oeba. Energy of antihelmintik is measured according to Lanson andBrown (1935) that is with soaking worm in 25 ml condensation which will be checked ( papaw seed extract with concentration of 100%, 50%, 25%, 10% and 5 %), then is observed number of dead worms in each hour clock. Data obtained of eachgroup of immersion will be tested with one track probit analysis and variant analysis. Result of inferential probit analysis that 1) Effective concentration (Efective Concentration/EC) from research to anthelmintic energy of papaw seed extract is 100%, 50%, 25%, 10% and 5%. Keywords: worm, seed extract, chicken